Association Between the Expression of MicroRNA-125b and Survival in Patients With Acute Coronary Syndrome and Coronary Multivessel Disease - Gager, Gloria M.; Eyileten, Ceren; Postula, Marek; Gasecka, Aleksandra; Jarosz-Popek, Joanna; Gelbenegger, Georg; Jilma, Bernd; Lang, Irene; Siller-Matula, Jolanta (Frontiers in Cardiovascular Medicine, 2022)
Background: MicroRNAs (miRNA, miR) have an undeniable physiological and pathophysiological significance and act as promising novel biomarkers. The aim of the study was to investigate blood-derived miRNAs and their association with long-term all-cause mortality in patients with multivessel disease (MVD) suffering from acute coronary syndrome (ACS). Methods: This study was an observational prospective study, which included 90 patients with MVD and ACS. Analysis of miRNAs expression miR-125a, miR-125b and miR-223 was conducted by polymerase chain reaction (PCR). Patients were followed-up for a median of 7.5 years. All-cause mortality was considered as the primary endpoint. Adjusted Cox-regression analysis was performed for prediction of events. Results: Elevated expression of miR-125b (>4.6) at the time-point of ACS was associated with increased long-term all-cause mortality (adjusted [adj.] hazard ratio [HR]=11.26, 95% confidence interval [95%CI]: 1.15-110.38; p=0.038). The receiver operating characteristic (ROC) analysis showed a satisfactory c-statistics for miR-125b for the prediction of long-term all-cause mortality (area under the curve [AUC]=0.76; p=0.034; the negative predictive value 98%). Kaplan-Meier time to event analysis confirmed an early separation of the survival curves between the groups (p=0.003). An increased expression of miR-125a and miR-223 was found in patients with non-ST-segment elevation ACS (NSTE-ACS) as compared to those with ST-segment elevation myocardial infarction (STEMI) (p=0.043 and p=0.049, respectively) with no difference in the expression of miR-125b between the type of ACS. Conclusion: In this hypothesis generating study, lower values of miR-125b were related to improved long-term survival in patients with ACS and MVD. Larger studies are needed to investigate whether miR-125b can be used as a suitable predictor for long-term all-cause mortality.